Automated synthesis of [68Ga]oxine, improved preparation of 68Ga-labeled erythrocytes for blood-pool imaging, and preclinical evaluation in rodents. Issue 3 (7th February 2018) - Thompson, Stephen; Rodnick, Melissa E.; Stauff, Jenelle; Arteaga, Janna; Desmond, Timothy J.; Scott, Peter J. H.; Viglianti, Benjamin L.
Abstract : Radiolabeled erythrocytes have multiple applications in nuclear medicine, including blood pool imaging. Abstract : Radiolabeled erythrocytes have multiple applications in nuclear medicine, including blood pool imaging. Historically they have been labeled with SPECT radionuclides. A PET blood pool imaging agent is highly desirable as it would improve clinical applications with better image quality and resolution, higher sensitivity, and dynamic scanning capabilities. With the coming of age of modern 68 Ge/ 68 Ga generator systems, gallium-68 is now widely accessible. In this paper we describe an updated method for the preparation of 68 Ga-labeled erythrocytes and their preliminary use in rodent blood pool imaging. A novel automated synthesis of [ 68 Ga]oxine using a 68 Ga/ 68 Ge generator and automated synthesis module is reported. [ 68 Ga]Oxine was synthesized in 50 ± 5% ( n = 3) non-decay corrected radiochemical yield and >99% radiochemical purity. Rat and human erythrocytes were successfully labeled with the complex in 42% RCY, and the 68 Ga-labeled erythrocytes have been shown to clearly image the blood pool in a healthy rat. Human erythrocytes labelled with [ 68 Ga]oxine were shown to be viable up to 2 hours post-labelling, and washout of the radiolabel was minimal up to 1 hour post-labelling. Further optimization of the labeling method to translate for use in human cardiac and oncologic blood pool PET imaging studies, is underway.